Examining the factors leading to the use of e-scooters in the context of micromobility - Fil, Mustafa Mert (My University, 2022)
Today, humanity demands more and more to live in cities. Better health, education, work and living conditions can be counted as important reasons for this. Due to this universal demand, which is valid all over the world, some problems have begun to emerge today. In cities where the population has increased uncontrollably, in addition to concrete problems such as traffic, air pollution, difficulty in accessing resources, unemployment and inability to find housing, social and psychological problems such as the feeling of being lost in the crowd or lack of belonging have begun to emerge. Related to all these problems, academics and those who design the future have revealed the concept of smart city. Thanks to smart cities, efficiency in areas such as transportation, air pollution and population planning in cities can be maximized, and social and psychological deformations can be minimized. Today, smart cities have been implemented as a concept in some pilot cities. One of the most effective ways to make cities smarter is to apply to micromobility solutions. Today, micromobility solutions have gained a rapidly expanding usage area. Along with the concept of micromobility, some solutions, which are also considered as sharing economy tools, have started to come into the service of people living in cities. Among these, e-scooters have an increasingly widespread use. This study aimed to understand what is the factors of e-scooter usage and continuance intention to use in Turkey. Technology Acceptance Model was accepted and this study managed new model that investigates after the e-scooter usage stages. To research, survey was done with 204 participants who used e-scooters before or still use. The survey questions created were statistically analyzed in SPSS and Smart PLS programs. As a result of the study, it was seen that saving time was effective in using e-scooters and continuance intention to use e-scooters. On the other hand, it turned out that when the participants started using e-scooters, they intended to continue to use it. When the other hypotheses of the study were tested, it was seen that male and female participants differed from each other on environmental awareness. Similarly, people aged 18-25 differed from those aged 26-35 in environmental awareness and energy conservation. It was observed that the participants differ in energy saving according to their education level.

Günümüzde insanlık, şehirlerde yaşamayı daha çok talep etmektedir. Bunun önemli sebepleri olarak daha iyi sağlık, eğitim, iş ve yaşam koşulları sayılabilir. Tüm dünyada geçerli olan bu evrensel talepten dolayı günümüzde bazı sorunlar ortaya çıkmaya başlamıştır. Nüfusun kontrolsüz arttığı şehirlerde trafik, hava kirliliği, kaynaklara ulaşmada sıkıntı, işsizlik ve konut bulamama gibi somut sıkıntıların yanı sıra kalabalıkta kaybolmuşluk hissi veya aidiyetsizlik gibi sosyal ve psikolojik sorunlar da ortaya çıkmaya başlamıştır. Bütün bu sorunlarla alakalı, akademisyenler ve geleceği tasarlayanlar, akıllı şehir kavramını ortaya çıkarmıştır. Akıllı şehirler sayesinde şehirlerdeki ulaşım, hava kirliliği, nüfus planlaması gibi alanlarda verimlilik en üst seviyeye çıkarılabilir, bu sayede de sosyal ve psikolojik deformasyonlar en az seviyeye indirilebilir. Günümüzde akıllı şehirler bazı pilot şehirlerde konsept olarak uygulamaya geçmiştir. Şehirlerin akıllanmasını sağlamadaysa en etkili yollardan biri mikromobilite çözümlerine başvurmaktır. Günümüzde mikromobilite çözümleri hızla yaygınlaşan bir kullanım alanına kavuşmuştur. Mikromobilite kavramıyla beraber, paylaşım ekonomisi aracı da sayılan bazı çözümler, şehirlerde yaşayan insanların hizmetine girmeye başlamıştır. Bunlarda e-scooter’lar, gittikçe yaygınlaşan bir kullanım ağına sahiptir. Bu çalışma, Türkiye'de e-scooter kullanımı ve kullanmaya devam etme niyetini etkileyen faktörlerin neler olduğu araştırılmıştır. Teknoloji Kabul Modeli kabul edilmiş ve bu çalışma, e-scooter kullanımından sonraki aşamalarını araştıran yeni bir modeli yönetmiştir. Araştırma için daha önce e-scooter kullanan veya halen kullanmakta olan 204 katılımcı ile anket yapılmıştır. Oluşturulan anket soruları SPSS ve Smart PLS programlarında istatistiksel olarak analiz edilmiştir. Çalışma sonucunda e-scooter kullanımında ve e-scooter kullanımına devam etme niyetinde zamandan tasarruf etmenin etkili olduğu görülmüştür. Öte yandan, katılımcıların e-scooter kullanmaya başladıklarında kullanmaya devam etmeyi düşündükleri ortaya çıkmıştır. Araştırmanın diğer hipotezleri test edildiğinde erkek ve kadın katılımcıların çevresel adanmışlık konusunda birbirlerinden farklılaştığı görülmüştür. Benzer şekilde, 18-25 yaş arası kişiler çevresel adanmışlık ve enerji tasarrufu açısından 26-35 yaş grubundan farklıydı. Katılımcıların eğitim seviyelerine göre enerji tasarrufu konusunda farklılık gösterdiği gözlemlenmiştir
Keywords: Business; İşletme